Performing autoethnography: An embodied methodological praxis - Spry, Tami (Qualitative Inquiry, 2001)
This article argues the personal/professional/political emancipatory potential of autoethnographic performance as a method of inquiry. Autoethnographic performance is the convergence of the “autobiographic impulse” and the “ethnographic moment” represented through movement and critical self-reflexive discourse in performance, articulating the intersections of peoples and culture through the innersanctions of the always migratory identity. The article offers evaluative standards for the autoethnographic performance methodology, calling on the body as a site of scholarly awareness and corporeal literacy. Autoethnographic performance makes us acutely conscious of how we “ Iwitness” our own reality constructions. Interpreting culture through the self-reflections and cultural refractions of identity is a defining feature of autoethnographic performance.
Number: 6
Keywords: approches et analyses; corps; discours dominant; ethnographie; identités; poésie; ressource en ligne; réflexivité; systèmes d'oppressions; thématiques; étude qualitative